2010
DOI: 10.1002/pssc.200982421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface Ga accumulation on the growth of GaN by molecular beam epitaxy

Abstract: We investigate the effect of surface Ga accumulation on the growth of GaN by molecular beam epitaxy (MBE) with ammonia as a nitrogen source. Control of the surface Ga condition is very important because the crystallization process strongly depends on the surface Ga coverage. The growth rate rapidly decreases when the supply of Ga exceeds certain amount when growing with ammonia, in contrast to the saturation grown with radio‐frequency plasma source. The critical Ga supply becomes higher by introducing the migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Today, there is common agreement that with Ga-rich MBE growth conditions a Ga double layer (bilayer) is formed on the GaN surface in which the mobility of Ga atoms is much higher than on a pure GaN surface. 9 Only recently, time-dependent variations of MBE, like pulsed MBE, 10 metal modulated epitaxy (MME), 11 or migration enhanced epitaxy (MEE), 12,13 have been reported which are taking advantage of that higher Ga atom mobility under specified Ga-rich growth conditions. In all those time-modulated MBE variants the flux of reactive nitrogen is interrupted periodically, while the Ga flux remains constant, leading to highly mobile excess Ga adatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is common agreement that with Ga-rich MBE growth conditions a Ga double layer (bilayer) is formed on the GaN surface in which the mobility of Ga atoms is much higher than on a pure GaN surface. 9 Only recently, time-dependent variations of MBE, like pulsed MBE, 10 metal modulated epitaxy (MME), 11 or migration enhanced epitaxy (MEE), 12,13 have been reported which are taking advantage of that higher Ga atom mobility under specified Ga-rich growth conditions. In all those time-modulated MBE variants the flux of reactive nitrogen is interrupted periodically, while the Ga flux remains constant, leading to highly mobile excess Ga adatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Ga adatoms had high sticking coefficients on the substrate at lower growth temperature. At elevated temperatures, surface Ga accumulation was less effective since Ga atoms can evaporate from the surface [28]. The accumulation of Ga atoms had high surface free energy to form nanoscale Ga droplets according to the Volmer-Weber (VW) growth model [29].…”
Section: Methodsmentioning
confidence: 99%
“…Migration enhanced epitaxy is a low temperature film growth method originally developed for use in the molecular beam epitaxy (MBE) of arsenide films, 10) but adapted to group III nitride film growth in 1997 by Hooper et al 11) For use of the technique for nitride film growth the less volatile metal precursor of a compound semiconductor is allowed extra time to migrate on the semiconductor surface to suitable lattice sites by adatom diffusion before dosing the growth front of the material with an active nitrogen species to form largely stationary compound molecules. 11) As evidenced by the work of many groups, [12][13][14][15][16] the adatom migration of the metal species allows material of improved crystal quality to be deposited. This film deposition is done in multiple cycles to build up the film thickness of the nitride compound.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally the migration enhanced epitaxy of nitride films is quite slow as only a wetting layer the thickness of a couple of monolayers of metal is deposited per cycle. 11,16) The mechanical switching of flows becomes a limiting factor, in a similar fashion to atomic layer epitaxy. However, recently it has been shown that quite thick metal layers can be deposited resulting in smooth semiconductor films despite the formation of small liquid metal droplets during the metal dosing process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation